Copper oxide-based nanoparticles in agro-nanotechnology: advances and applications for sustainable farming - Naweedullah Amin; Khalida Aziz (Agriculture & Food Security)
Abstract Feeding the world's population sustainably and addressing food insecurity are among the most pressing global challenges. Agriculture, a key sector in addressing these challenges, faces disease outbreaks, inefficient fertilizer use, and adverse environmental impacts. This review explores the green synthesis and sustainable application of copper oxide nanoparticles (CuO NPs) in agriculture, focusing on their role as nanoagrochemicals. The green synthesis of CuO NPs using plant extracts produces nanoparticles (NPs) with tailored properties that enhance their efficacy as nanoagrochemicals. Copper oxide NPs have shown promising applications as nanopesticides, providing potent antimicrobial and antifungal effects, primarily through reactive oxygen species (ROS) generation, which disrupts cellular functions in pathogens. Moreover, CuO NPs improve plant growth by enhancing nutrient uptake and photosynthetic efficiency, making them effective nanofertilizers. Furthermore, nanopriming, an innovative seed treatment using CuO NPs, enhances seed germination and plant growth by activating stress-related genes and improving biochemical responses, especially under drought and salinity. Studies demonstrate the superior efficacy of CuO NPs over conventional agrochemicals in enhancing seedling vigor, nutrient uptake, and crop yield. However, concern regarding phytotoxicity at higher concentrations and potential environmental impacts necessitate careful dosage optimization. This review provides insights into the sustainable application of CuO NPs in agriculture, highlighting their potential to revolutionize crop productivity while emphasizing the need for further research into long-term environmental safety and optimized application methods.